2018
DOI: 10.1021/acscombsci.8b00030
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial Synthesis and High-Throughput Characterization of Fe–V–O Thin-Film Materials Libraries for Solar Water Splitting

Abstract: The search for suitable materials for solar water splitting is addressed with combinatorial material science methods. Thin film Fe-V-O materials libraries were synthesized using combinatorial reactive magnetron cosputtering and subsequent annealing in air. The design of the libraries comprises a combination of large compositional gradients (from FeVO to FeVO ) and thickness gradients (from 140 to 425 nm). These material libraries were investigated by high-throughput characterization techniques in terms of comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 35 publications
4
24
0
Order By: Relevance
“…[17,18] This exciting prospect has generated extensive high-throughput and combinatorial efforts to accelerate the discovery and study of new complex metal oxides photo absorbers for solar water splitting. [19][20][21][22][23][24] However, with rapidly increasing efforts toward finding new ideal compositions of photoabsorbers with enhanced properties, the number of different cations is very probable to increase. The cations may vary widely in size, oxidation state, and vapor pressure under heating treatment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] This exciting prospect has generated extensive high-throughput and combinatorial efforts to accelerate the discovery and study of new complex metal oxides photo absorbers for solar water splitting. [19][20][21][22][23][24] However, with rapidly increasing efforts toward finding new ideal compositions of photoabsorbers with enhanced properties, the number of different cations is very probable to increase. The cations may vary widely in size, oxidation state, and vapor pressure under heating treatment conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Several groups have reported the fabrication of FeVO 4 thin films using magnetron cosputtering, spray pyrolysis, dropcasting, and sol-gel methods with reported bandgap energy of 2.0-2.1 eV. [21][22][23][24][25][26][27][28][29][30][31] However, the achieved photocurrents are still very low as compared with the theoretical photocurrent based on the bandgap energy. We have previously identified that the main problem causing the low performance of FeVO 4 films is the poor bulk carrier separation.…”
Section: Introductionmentioning
confidence: 99%
“…In this system it was found by high-throughput experimentation and ab initio calculations that the addition of Cu improves the alloy properties. 21 (copyright ACS Publications, 2014), 49 (copyright ACS Publications, 2017), 58 (copyright ACS Publications, 2017), 59 (copyright Elsevier, 2012), 60 (copyright ACS Publications 2018) and 37 (copyright RCS, 2018)…”
Section: Exemplary Resultsmentioning
confidence: 99%